1984
DOI: 10.1021/np50034a004
|View full text |Cite
|
Sign up to set email alerts
|

Cmr Spectroscopy of Labdanic Diterpenes and Related Substances

Abstract: A carbon-shift analysis of labdanic diterpenes of the manool, agathic acid, and sciadin types is presented. The C-12 and C-20 configurations of sciadin have been determined and the structure of potamogetonin has been revised. 'Dedicated to Professor Edgar Lederer on the occasion of his seventy-fifth birthday. 2Carbon-13 Nuclear Magnetic Resonance Spectroscopy of Naturally Occurring Substances, LXXXI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 15 publications
5
38
0
Order By: Relevance
“…The HMBC spectrum indicated that these oxirane protons have a 1 H-13 C interaction with the quaternary C8 position, and, in the COSY spectra, a 4 J 1 H-1 H coupling was observed between the downfield oxirane proton (δ H 2.82 ppm) and one of the C7 protons (δ H 1.92 ppm). Similar chemical shifts were observed in several other labdanes [31][32][33][34][35][36] with a spiro-epoxy group at C8. Another downfield resonance was observed at δ C 83.8 ppm, which is consistent with an allylic alcohol, with the position established as C12 using the HMBC spectrum.…”
Section: Structural Characterisation Of Diterpenes 4-8supporting
confidence: 84%
“…The HMBC spectrum indicated that these oxirane protons have a 1 H-13 C interaction with the quaternary C8 position, and, in the COSY spectra, a 4 J 1 H-1 H coupling was observed between the downfield oxirane proton (δ H 2.82 ppm) and one of the C7 protons (δ H 1.92 ppm). Similar chemical shifts were observed in several other labdanes [31][32][33][34][35][36] with a spiro-epoxy group at C8. Another downfield resonance was observed at δ C 83.8 ppm, which is consistent with an allylic alcohol, with the position established as C12 using the HMBC spectrum.…”
Section: Structural Characterisation Of Diterpenes 4-8supporting
confidence: 84%
“…3,25 These isomers showed essentially identical NMR spectral properties for ring skeletal proton and carbon signals and only differed in signals attributable to the side chain. Comparison with NMR spectral properties of other E and Z isomers of labdane diterpenes 15,16 and from the literature 13,14,27 confirmed the structure of 4E. Isomer 4Z was unknown.…”
Section: Resultssupporting
confidence: 57%
“…The 1 H and 13 C NMR spectra (CDCl3) and correlations observed from the NOESY spectrum of potamogetonyde (3) and potamogetonol (4). This material is available free of charge via the Internet at http://pubs.acs.org.…”
Section: Acknowledgmentmentioning
confidence: 99%